Rancang Bangun Sistem Informasi Manajemen Terpadu (SIMANTEP) Online PT. PLN (Persero) Sektor Pembangkitan Tarahan Lampung Dengan Metode Extreme Programming - Muludi, Kurnia; Irawati, Anie Rose; Candra, Bayu Ade (Jurnal Komputasi, 2013)
SMTâs secretariat is one of the PT. PLN (Persero) Power Generation Sector of Tarahan which is responsible for document control process. The documents control form start from submission until distribution are still in manual process, for example, the distributed documents still in the hardcopy. This research creates the Integrated Management Information System or SIMANTEP Online which is an integrated information system that gave online service of documents management at PT. PLN (Persero) Power Generation Sector of Tarahan Lampung. The information system is made using Extreme Programming (XP), one of Agile Development Methods. The result of this research is an online information system which is not only accessible in Tarahan PLTUâs office area, but also can be accessed by the internet. The SIMANTEP Online also provides convenience for the user in terms of documents management and control, start from the submission, validation, and distribution of documents with online service.Â Keywords: Agile Development Methods, Extreme Programming, Information Systems, Management of Documents, PLN.